2012
DOI: 10.1021/ja310323y
|View full text |Cite
|
Sign up to set email alerts
|

o-Fluoroazobenzenes as Readily Synthesized Photoswitches Offering Nearly Quantitative Two-Way Isomerization with Visible Light

Abstract: Azobenzene functionalized with ortho-fluorine atoms has a lower energy of the n-orbital of the Z-isomer, resulting in a separation of the E and Z isomers' n→π* absorption bands. Introducing para-substituents allows for further tuning of the absorption spectra of o-fluoroazobenzenes. In particular, electron-withdrawing ester groups give rise to a 50 nm separation of the n→π* transitions. Green and blue light can therefore be used to induce E→Z and Z→E isomerizations, respectively. The o-fluoroazobenzene scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
750
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 756 publications
(789 citation statements)
references
References 24 publications
27
750
1
11
Order By: Relevance
“…Such compounds were reported in Bushuyev et al [65]. In the material design, useful suggestions given in Bléger et al [66] were taken into account, as it was found that extremely long cis-isomer half-lives are characteristic of o-fluorinated azobenzenes. Symmetrically substituted 4-haloperfluoro azobenzenes were thus prepared (Fig.…”
Section: Halogen-bonded Crystals That Movementioning
confidence: 95%
“…Such compounds were reported in Bushuyev et al [65]. In the material design, useful suggestions given in Bléger et al [66] were taken into account, as it was found that extremely long cis-isomer half-lives are characteristic of o-fluorinated azobenzenes. Symmetrically substituted 4-haloperfluoro azobenzenes were thus prepared (Fig.…”
Section: Halogen-bonded Crystals That Movementioning
confidence: 95%
“…Various structures for bistable azobenzene photoswitches have been developed, 1417 and, among them, ortho -fluorinated azobenzenes appear particularly promising. 14,15 Fluorination is also an effective strategy to tailor the anisotropy and viscoelastic properties of LCs, 18,19 and boost intermolecular interactions for the self-assembly of supramolecular LCs. Combining these design principles, here, we target a new family of azobenzene-based, fluorinated supramolecular LCs with predictable phase behavior and efficient light-control over the molecular alignment.…”
Section: Introductionmentioning
confidence: 99%
“…The power of azobenzenes lies in the fact that the lifetime of the metastable cis -isomer can be controlled over a wide range, from milliseconds in push–pull azobenzenes 14 up to even several months in ortho -substituted azobenzenes. 15 While fast thermal relaxation is useful in, for example, optical switching 16 and the long-lived cis -state desired in photobiology, 17 azobenzene derivatives whose thermal isomerization dynamics depends strongly on the environmental conditions are particularly interesting. As the most prominent example, 4-hydroxyazobenzenes can experience a change of up to 5 orders of magnitude in the cis -lifetime in nonpolar versus polar solvents due to hydrogen-bond-assisted tautomerization.…”
mentioning
confidence: 99%